The leader's shadow : exploring and developing executive character - Judge, William Q. (Sage Publications, 1999)
This is the first book to examine fully the inner dynamics of executives in top leadership positions. This empirical examination of the character of leaders covers areas such as personality, values and spirituality, and has been conducted through surveys and in-depth interviews. The reader is invited to combine the information gleaned from the life stories of the interviewed CEOs with personal reflection as a first step in developing his or her own leadership character.